Cerebral hyperperfusion syndrome following carotid endarterectomy - Thomas Saliba; Olivier Cappeliez; Henri Maisonnier; Sanjiva Pather; Ilias Bennouna (Swiss Journal of Radiology and Nuclear Medicine)
Introduction: Cerebral hyperperfusion syndrome (CHS) is a rare but potentially fatal complication following carotid revascularization procedures, particularly carotid endarterectomy (CEA), which is commonly used to treat extracranial carotid stenosis, which is a cause of approximately 15% of all strokes. CHS is characterized by non-ischemic headaches, seizures, and neurological deficits.